Great Society (Czech Journal of International Relations, 1967)
The possibility of obtaining information about the problems of the United States of America for the Czech reader in recent years 112 so rare. Works by historians (N. N. Inozemcev, J. Volek), soldiers (O. Mahler, H. Kahn), sociologists (I. Dubská), publicists (P. Tva-roh, D. Pokorný) or writers (M. Ho-lub) and the articles and studies of many others make it possible, at least indirectly, to get acquainted with the issues of this world power, which is very distant for most of us due to normal communication. Recently, another contribution has been added to these views by the historian J. Volk, who in the library of the Alphabet of International Relations (in one of their final volumes) deals with the internal politics - and we will say right away, very successfully - of the American presidents I.F. Kennedy and L.B. Johnson.The author chose the "Great Society" of the current president as his main topic, who wanted to differentiate himself from his predecessor even in the name of his policy. Volek primarily wanted to "explain the questions of the internal, economic, social and above all political situation with an emphasis on the analysis of the concept of the Great Society". Regarding the origin of the invitation, I would like to draw attention to the interesting work of the Moscow IMEMO workers' collective,) where the authors mention the Great Society already in 1914 (Graham Wallace's book), but I see the theoretical basis for John's program in the work of Prof. Galbraith.